Seven pillars of the piano technique (Orfeu, 2021)
Piano technique has been widely discussed, and yet we are frequently confronted with outmoded beliefs concerning its dependence on factors such as natural talent, repetitive effort or hand size. The perpetuation of these antiquated notions can culminate in pain, injury, emotional problems, and even the definitive interruption of any artistic activity. This article aims to analyze and systematize approaches that strive for a healthy, rational and musical ways of thinking piano technique and categorize them into seven pillars: body posture, movement coordination, arm functions, including semi-circular and rotational  ovements, lateral displacement on the keyboard and note grouping for enhanced cognition and technical mastery. It is concluded that, despite of small disagreements between the authors, there is a convergence in the search of pianistic efficacy through  hysical well-being, translated into the development of body awareness and, consequently, in the quality and  ariety of sound. The categorization of the pillars, in turn, promotes easier access to the analyzed concepts and allows greater efficiency in their application.
Keywords: piano technique; corporal conscience; categories of healthy and efficient movements